Heatwave - Redniss, Lauren (2024)
An almost unbearably hot day of one hundred degrees is transformed as raindrops fall one by one, culminating in a downpour
Ages 4-8.
Keywords: Weather -- Juvenile fiction; Heat -- Juvenile fiction; Storms -- Juvenile fiction; Rain and rainfall -- Juvenile fiction; picture books; Picture books; Picture books; Livres d'images.